1987
DOI: 10.1007/bf00450459
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the stability of anterior and posterior cervical spine fixation procedures

Abstract: Both posterior and anterior procedures of stabilization are used for operative immobilization of unstable functional units of the cervical spine. The primary stabilizing effect of each procedure was examined and the two were compared in an experimental study. To this end the functional units C-5 and C-6 were removed from ten fresh cervical spines, the discoligamentous structures being preserved, and C-6 was embedded in methacrylate. As a result of a tensile force in a vertical direction applied to the base of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
8

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 19 publications
1
21
0
8
Order By: Relevance
“…In contrast, earlier biomechanical studies [11,28,32] have shown disrupted and then anteriorly stabilized cervical spines to be less stable than intact specimens. In tests of immediate stability in segments fixed with Caspar plates secured with 3.5-mm unicortical or bicortical screws in a constrained testing system, Ryken et al [27] found no significant differences between the two types of screw fixation.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast, earlier biomechanical studies [11,28,32] have shown disrupted and then anteriorly stabilized cervical spines to be less stable than intact specimens. In tests of immediate stability in segments fixed with Caspar plates secured with 3.5-mm unicortical or bicortical screws in a constrained testing system, Ryken et al [27] found no significant differences between the two types of screw fixation.…”
Section: Discussionmentioning
confidence: 68%
“…Despite this, anterior plate systems with bicortical screw fixation have been repeatedly cited for the potential to cause neurologic injuries due to posterior cortex perforation [2,25,27,29]. Also, biomechanical studies have suggested that anterior plate fixation alone was insufficient when posterior structures were injured [11,13,30,32].…”
Section: Wolfgang Lehmann Michael Blauth Daniel Briem Ulf Schmidtmentioning
confidence: 99%
“…4,6,7,17,25,29,31 Do Koh et al compared anterior and posterior plate fixation in a biomechanical study. 6 They found that anterior fixation with interbody grafting failed to provide stabilization and concluded that posterior plating leads to better stability than anterior plating with locked fixation screws.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral mass plating is widely accepted as one of the posterior fixation methods for the lower cervical spine fractures from the C3 through C7 vertebrae [2]. This approach is also useful for instability occurring after multiple-level anterior cervical fusion, multiple laminectomies due to myelopathy, cervical tumor removal, and surgery for degenerative diseases [1,2,25]. Although excellent results have been reported using lateral mass screw plating, neurovascular complications may potentially result from this approach because of its anatomic proximity to vital structures, such as the vertebral artery, cervical nerve root, and spinal cord [2,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is also useful for instability occurring after multiple-level anterior cervical fusion, multiple laminectomies due to myelopathy, cervical tumor removal, and surgery for degenerative diseases [1,2,25]. Although excellent results have been reported using lateral mass screw plating, neurovascular complications may potentially result from this approach because of its anatomic proximity to vital structures, such as the vertebral artery, cervical nerve root, and spinal cord [2,24,25]. However, brain complication of cerebellar or brain stem infarction is very rare, although the screwing procedure injures the vertebral artery during the operation.…”
Section: Introductionmentioning
confidence: 99%